2011
DOI: 10.1016/j.abb.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of nonmelanoma skin cancers in organ transplant recipients

Abstract: Nonmelanoma skin cancer (NMSC) is the most common human cancer, with an incidence of more than 1.2 million per year in the U.S.A. The risk for the development of NMSCs increases by approximately 10-250 fold in chronically immune suppressed organ transplant recipients (OTRs). Solar UVB is the most common etiologic factor in the development of this neoplasm, both in immune competent and immune suppressed populations. This review provides a description of NMSC in OTRs. It also provides an account of the various i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
66
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 48 publications
4
66
0
2
Order By: Relevance
“…Exposure to ultraviolet radiation (UVR) is a major risk factor in the development of these skin cancers and acts as both a mutagen and an immune suppressing agent (4, 5). The effect of immunosuppression on skin cancer occurrence is highlighted in organ transplant recipients who are at high risk for the development of squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) (rev in (6)). In addition, observations of spontaneous BCC regression underscore the importance of the immune response to tumor antigens in tumor progression (7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to ultraviolet radiation (UVR) is a major risk factor in the development of these skin cancers and acts as both a mutagen and an immune suppressing agent (4, 5). The effect of immunosuppression on skin cancer occurrence is highlighted in organ transplant recipients who are at high risk for the development of squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) (rev in (6)). In addition, observations of spontaneous BCC regression underscore the importance of the immune response to tumor antigens in tumor progression (7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Adicionalmente, os fĂĄrmacos imunossupressores utilizados para induzir tolerĂąn-cia ao ĂłrgĂŁo transplantado podem desempenhar um papel fundamental na carcinogĂ©nese pelos seguintes mecanismos: redução da vigilĂąncia imunolĂłgica, com proliferação e aumento da sobrevivĂȘncia de cĂ©lulas atĂ­picas; o efeito carcinogĂ©nico direto de fĂĄrmacos, como a azatioprina e ciclosporina; e proliferação de vĂ­rus oncogĂ©nicos. 6 O rim Ă© o ĂłrgĂŁo sĂłlido mais frequentemente transplantado em Portugal e este procedimento associa-se a um risco de CCNM superior ao da transplantação de fĂ­gado, mas inferior Ă  de pulmĂŁo ou coração, o que Ă© explicado, em parte, pela necessidade de diferentes intensidades de imunossupressĂŁo. [4][5][6] Nas Ășltimas dĂ©cadas tĂȘm sido feitos esforços no sentido de reduzir o risco de CCNM decorrente da transplantação renal.…”
Section: Introductionunclassified
“…6 O rim Ă© o ĂłrgĂŁo sĂłlido mais frequentemente transplantado em Portugal e este procedimento associa-se a um risco de CCNM superior ao da transplantação de fĂ­gado, mas inferior Ă  de pulmĂŁo ou coração, o que Ă© explicado, em parte, pela necessidade de diferentes intensidades de imunossupressĂŁo. [4][5][6] Nas Ășltimas dĂ©cadas tĂȘm sido feitos esforços no sentido de reduzir o risco de CCNM decorrente da transplantação renal. Os fĂĄrmacos conhecidos como inibidores da mammailan target of rapamycin (mTOR) -sirolimus e everolimus -nĂŁo sĂŁo nefrotĂłxicos, apresentam inerentemente propriedades antineoplĂĄsicas e antiangiogĂ©nicas e, ao bloquearem a proliferação dos linfĂłcitos B e T, atuam como imunossupressores.…”
Section: Introductionunclassified
“…A study 5 in heart transplant recipients found that 89% of skin cancers in this population were SCC, while 11% were BCC. The prevailing theory for skin cancer development in SOTRs is that due to diminished immune surveillance, an enhancement of UVinduced DNA damage allows atypical cells to survive and proliferate 6,7 . This theory is supported by Ducloux et al 8 , who discovered that renal transplant recipients with skin cancers had significantly lower mean CD4+ T-cell counts than those without skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that immunosuppression is not a sufficient explanation for skin cancer development in SOTRs. The contribution of carcinogenic immunosuppressants and oncogenic viral infections are also thought to contribute to skin cancer development 6 . SOTRs are at increased risks of human papillomavirus (HPV) and although an association between HPV and SCC has been described, ongoing research suggests that the link is not as clear 10 .…”
Section: Introductionmentioning
confidence: 99%